2017
DOI: 10.5977/jkasne.2017.23.4.430
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Among Moral Distress, Physical Symptoms and Burnout of Hospital Nurses

Abstract: Purpose: The purpose of this study was to explore the relationship between moral distress, physical symptoms, and burnout among clinical nurses. Methods: Data were collected by self-report questionnaires targeting 140 nurses from a university hospital in Chungju. The data were analyzed by, Kruskal-Wallis, Pearson correlation coefficient, and stepwise multiple regression. Results: Moral distress due to the general characteristics of the participants showed a statistically significant difference at the current w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
1
5
0
1
Order By: Relevance
“…Concerning job‐related features, the greater the level of exhaustion in the participants' position as general nurses, the more dissatisfied they were with their jobs, and the more they intended to find another job. These findings align with previous research in which general nurses experienced burnout more than head nurses (Chae et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Concerning job‐related features, the greater the level of exhaustion in the participants' position as general nurses, the more dissatisfied they were with their jobs, and the more they intended to find another job. These findings align with previous research in which general nurses experienced burnout more than head nurses (Chae et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…The Korean version of the Moral Distress Scale-Revised (KMDS-R) validated by Chae et al [ 33 ] using the Moral Distress Scale-Revised (MDS-R) developed by Hamric et al [ 34 ], was used. Permission to use the KMDS-R was granted by Hamric and Chae.…”
Section: Methodsmentioning
confidence: 99%
“…A higher score indicated a stronger sense of moral distress. Hamric et al [ 34 ] and Chae et al [ 33 ] reported Cronbach’s alpha reliabilities of 0.89 and 0.91, respectively. This study supported the KMDS-R’s reliability with a Cronbach’s α = 0.85.…”
Section: Methodsmentioning
confidence: 99%
“…A Korean version of the Moral Distress Scale-Revised (KMDS-R) was employed, which was validated by Chae et al [ 33 ] from the Moral Distress Scale-Revised (MDS-R) developed by Hamric et al [ 34 ] for nurses. Permission to use the KMDS-R was granted by Dr. Hamric and Dr. Chae.…”
Section: Methodsmentioning
confidence: 99%
“…The number of points of moral distress was calculated as the total score by adding all the scores of each question; a higher score indicates a stronger sense of moral distress. Hamric, Borchers and Epstein [ 34 ] reported a Cronbach’s alpha reliability of 0.89, and Chae, Yu, Lee and Park [ 33 ] found a reliability of 0.91. In this study, the KMDS-R reliability was generated with a Cronbach’s alpha of 0.85.…”
Section: Methodsmentioning
confidence: 99%